Case of anisakiasis presenting as an Amyand hernia. Issue 7 (8th July 2020) - Hope, William; Smith-Chakmakova, Faye; Snyder, Justin
Abstract : This is a case of a 31-year-old male patient who presented with signs and symptoms of an incarcerated inguinal hernia. The patient's preoperative imaging showed a tubular structure in the inguinal canal and given the patient's history at presentation, there was a concern for herniation of the appendix, known as an Amyand hernia. On laparoscopy, there was no evidence of appendiceal involvement and a standard open inguinal hernia was completed. On the final pathology of the hernia sac, roundworms were identified with Y-shaped lateral cords suggesting infection by Anisakis spp. On a further interview with the patient, he revealed that he had recently travelled to Alaska and had consumed raw salmon on a fishing trip. This case demonstrates the importance of a thorough social and travel history. One should also have a low threshold to broaden the differential diagnosis when medical work-up deviates from the standard course.